2019
DOI: 10.1016/j.celrep.2019.02.050
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-B Is Required for Development of the Glymphatic System

Abstract: Highlights d The glymphatic system is first developed in the hippocampus d Insufficient PDGF-B signaling decreases AQP4 polarization to astrocyte vascular endfeet d Insufficient PDGF-B signaling impairs maturation of the glymphatic function

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 69 publications
4
103
0
Order By: Relevance
“…However, it remains enigmatic whether or not AQP4 is solely responsible for this fluid transport or not (Lendahl et al, 2019). Recently, insufficient PDGFB signaling in the Pdgfb ret/ret mice has shown decreased pericyte coverage of the vessels with decreased AQP4 polarization to astrocyte endfeet, which impairs maturation of the glymphatic function (Munk et al, 2019). The focal absence of pericytes correlates with relocation of AQP4 from astrocytic endfeet to the soma of astrocytes (Armulik et al, 2010).…”
Section: Clearance Of Materials From the Brainmentioning
confidence: 99%
“…However, it remains enigmatic whether or not AQP4 is solely responsible for this fluid transport or not (Lendahl et al, 2019). Recently, insufficient PDGFB signaling in the Pdgfb ret/ret mice has shown decreased pericyte coverage of the vessels with decreased AQP4 polarization to astrocyte endfeet, which impairs maturation of the glymphatic function (Munk et al, 2019). The focal absence of pericytes correlates with relocation of AQP4 from astrocytic endfeet to the soma of astrocytes (Armulik et al, 2010).…”
Section: Clearance Of Materials From the Brainmentioning
confidence: 99%
“…The role of Aqp4 in glymphatic function is, however, still a matter of discussion. The development of a functional glymphatic system in mice was shown to be correlated with the expression of Aqp4 at the astrocyte endfoot-vascular interface [62], and using several lines of Aqp4deficient mice, glymphatic tracer transport was shown to depend on intact Aqp4 function [63]. It has, however, also been argued that Aqp4 may not be solely responsible for fluid transport, but that diffusion is in fact an important regulator of paravascular flow.…”
Section: Paravascular Flowmentioning
confidence: 99%
“…Do pericytes play a role in the glymphatic system? A recent analysis of pericyte-deficient Pdgfb ret/ret mice shows a defective development and persistence of glymphatic function, suggesting that PDGFB signaling plays an important role in the development of the glymphatic system [62]. It is likely that this role is mediated by pericytes, since the local absence of pericytes in Pdgfb ret/ret mice correlates with relocation of Aqp4 from astrocyte endfeet to the astrocyte cell soma at these sites [20].…”
Section: Paravascular Flowmentioning
confidence: 99%
“…Van Veluw et al [92] have recently provided evidence on the importance of vasomotion in the clearance of solutes from brain in awake mice. New tools for studying the glymphatic system are welcome and Munk et al [93] have recently identified platelet-derived growth factor-B as being essential for glymphatic development.…”
Section: Csf and Glymphatic Dynamicsmentioning
confidence: 99%